A Ubiquitous Motion Tracking System Using Sensors in a Personal Health Device - KeeHyun Park (International Journal of Distributed Sensor Networks)
A motion tracking system for objects can track and display the movement of objects, including sporting equipment. Recently, it has become evident that individuals who actively participate in sport or fitness activities can benefit from the feedback provided by such a system. A motion tracking system for sporting equipment can improve the sporting skills of users and help prevent injury. In this study, a ubiquitous motion tracking system that tracks sporting equipment using the sensors installed in an activity monitor is proposed and constructed. The activity monitor with the tracking sensors can be attached to places on the body or on sports equipment to calculate the speed and acceleration of these objects. The ubiquitous motion tracking system consists of four modules: a tracking sensor module and a communication module in an activity monitor, a communication module in a USB dongle, and a motion analyzer module in a laptop PC. For experiments, an activity monitor with the tracking sensor module and the communication module is attached to a golf club, and a golf swing is taken. The results of the experiments show that the motion data of sporting equipment can be captured and analyzed easily, in both an indoor environment and an outdoor environment.